A Semiotic Study of Duan Inkstones as Tourist Souvenirs from the Tourists' Perspectives - Wu, Caixia (Nurture, 2026)
This paper examines Duan inkstones, a traditional cultural artifact from Guangdong, China, as tourist souvenirs through a semiotic lens. By analyzing the symbolic meanings, cultural connotations, and aesthetic expressions embedded in Duan inkstones, the study explores how tourists perceive and interpret these artifacts in the context of cultural tourism. Drawing on semiotic theory, the paper identifies three layers of meaning in Duan inkstones: material symbolism, cultural symbolism, and experiential symbolism. This study holds significant academic value and practical implications. Through interviews with tourists and analysis of purchasing behaviors, the study reveals that tourists value Duan inkstones not only for their artistic and historical significance but also for their role in constructing cultural identity and facilitating cross-cultural communication. The findings suggest that Duan inkstones serve as semiotic bridges connecting tourists to Chinese culture, offering insights into the dynamics of cultural consumption in tourism. It constructs a theoretical model to explore pathways for their visual transformation and material reconstruction, providing a methodological approach for differentiated innovation in souvenir design, and practically enhancing the cultural connotations and aesthetic qualities of such souvenirs and thereby strengthen their market competitiveness.